دراسة تصنيفية لأنواع فوق عائلة Arietelloidea من رتبة (Calanoida) في المياه البحرية الساحلية لمدينة اللاذقية - بطل, محمد مجاهد; شاغوري, غالية; ضرغام, هاني (Latakia University Journal -Basic Sciences Series, 2018)
This study was performed on the superfamily Arietelloidea (order Calanoida) which forms a major part in marine food chains of fish. The present study is the first in the Syrian marine coastal water and is considered a contribution to the study of the Syrian marine biodiversity. The samples were collected from 7 stations by vertical haul. We defined 9 species belonging to 4 genera and 4 families, These species are : Euaugabtilus hecticus (Giesbrecht), Lucicutia flavicornis (Claus), L. gimina Farran, L. ovalis (Gisbrecht), Pleuromamma gracilis (Claus), P. abdominalis (Lubbock), L. longicornis (Giesbrecht), L. curta Farran & Heterorabdus papilliger (Claus). The last three species are new in Syria ; but the last one was recorded in Lebanon. <!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]--> أجريت دراسة تصنيفية لأنواع فوق عائلة Arietelloidea من رتبة Calanoida التي تشكل حلقة أساسية في السلسلة الغذائية للأسماك ويعد هذا البحث الأول من نوعه في المياه البحرية الساحلية ، وهو مساهمة في دراسة التنوع الحيوي البحري السوري. تم الإعتيان بطريقة الجمع العمودي للمياه البحرية الساحلية لمدينة اللاذقية من سبع محطات مختلفة. تم تحديد 9 أنواع تنتمي إلى 4 أجناس و4 عائلات وهي : Euaugabtilus hecticus (Giesbrecht), Lucicutia flavicornis (Claus), L. gimina Farran, L. ovalis (Gisbrecht), Pleuromamma gracilis (Claus), P. abdominalis (Lubbock), L. longicornis (Giesbrecht), L. curta Farran & Heterorabdus papilliger (Claus). و تسجل الأنواع الثلاثة الأخيرة لأول مرة في سورية ولكن النوع الأخير سجل لأول مرة في المياه البحرية اللبنانية.